A Framework for Evaluating Deployed Security Systems: Is There a Chink in your ARMOR? - Taylor, M.E.; Kiekintveld, C.; Western, C.; Tambe, M. (Informatica)
A Framework for Evaluating Deployed Security Systems: Is There a Chink in your ARMOR?